KESESUAIAN ANTARA RENCANA PELAKSANAAN PEMBELAJARAN DENGAN PELAKSANAAN PEMBELAJARAN PADA GURU MATEMATIKA KURIKULUM 2013 - Fitriani Nur; Fitria Fitria; Nur Khalisah Latuconsina; Lisnasari Andi Mattoliang; Ahmad Farham Majid (Universitas Islam Negeri Alauddin Makassar, 2020)
The study aims to find out the suitability of the mathematics teachers’ lesson plan with the 2013 curriculum, the mathematics teachers’ learning implementation with the 2013 curriculum, and the lesson plan with the mathematics teacher’s learning activities with the 2013 curriculum. The study used descriptive research with qualitative approach. The research subjects were 3 mathematics teachers of class X in the State Senior High School (SMAN) 11 Makassar. The documentation, observation sheet, and interview guidelines were the instruments used in this study. The analysis results of the lesson plan with the learning activities based on the 2013 curriculum in accordance with the cultural and education ministry regulation number 22 of the year 2016 about the Elementary and Secondary Education Standard Processes showed that the suitability of those three mathematics teachers’ lesson plans with the learning implementation of the 2013 curriculum was categorized as very high with the percentage of 94.44%, the suitability of the learning implementation in SMAN 11 Makassar at class X with the learning implementation of the 2013 curriculum was categorized as high with the percentage of 81.68%, and the suitability of the lesson plan with the learning implementation based on the 2013 curriculum in SMAN 11 Makassar at class X was categorized as low with the percentage of 62.17%. The study finding also indicated that there was unsuitability between the lesson plan and the mathematics teachers’ learning implementation of the 2013 curriculum at class X of SMAN 11 Makassar.